A new genus of Zodariidae (Arachnida: Araneae) from Tajikistan - Zamani Alireza; Marusik Yuri M. (Taylor & Francis, 2025)
The new zodariid genus Spinozodium gen. nov. is described, comprising two species from Tajikistan: the type species S. denisi (Spassky, 1938) comb. nov. (ex. Zodarion Walckenaer, 1826) and the new species S. khatlonicum sp. nov.; the female of the type species, displaying highly reduced receptacles, is described for the first time. Both species are illustrated and their distributions are mapped, and keys to the Middle Asian zodariid subfamilies and genera are provided.